Molecular simulation of effect of cross-linking density on the properties of nitrile rubber - HE Shi-yao, WANG hui-ming, WANG Shi-jie, CUI Jian-zheng (Editorial Office of China Synthetic Rubber Industry, 2021)
Based on molecular dynamics(MD), nitrile rubber(NBR) models with cross-linking densities of 0, 10%, 15% and 20% were established, and the glass transition temperature and mechanical property of the NBR model under different cross-linking densities were predicted.The results showed that the glass transition temperature of NBR with a cross-linking density of 0-20% increased with increasing cross-linking density, and the mechanical property first increased and then decreased with the increase of cross-linking density. When the cross-linking density was 10%, NBR could obtain the optimal cross-linking network structure, and its mechanical property was better.